Qualidade de carne e ocorrência de pododermatite em frangos de corte criados em cama com acidificante em diferentes períodos sazonais - Lima, Juliana de Fatima Pereira de (2018)
Qualitative parameters of broilers meat the foot pad dermatitis incidence is directly related to the welfare of broilers. In this way, the poor quality of the litter changes the microenvironment exposing the broiler to a situation of stress, in addition to being an aggravating factor for the footpad dermatitis incidence. Therefore, the use of acidifying is a strategy to promote a pleasant environment to broiler during the different periods climatic. In this sense, the chapter 1 (literature review), aimed to address factors related to the quality of the broiler and your litter interference on broiler welfare, emphasizing the footpad dermatitis incidences and the quality characteristics chicken of meat. And in Chapter 2, the objective of assessing the influence of different seasonal periods and the use of chemical treatment with acidifying features on physical quality of litter, the footpad dermatitis incidence and meat quality of broilers. To this end, four consecutive seasonal periods were evaluated throughout the year using four aviaries per cycle, with a density of creation of 12 birds/m². The litter of two of the aviaries was treated with the compound based on calcium sulfate activated with sulfuric acid and expanded filosilicate, applied on the surface of the litter in two steps (before the accommodation of birds and 12 days of age of birds) in each cycle. A completely randomized design with the 4X2 factorial scheme was used to evaluate the qualitative parameters and the sensorial analysis of meat, subdivided parcel scheme in time with factorial on the parcel (5x2) to the reviews of moisture and surface temperature of the litter and was used two treatments (acid litter and litter without treatment) and seasonal periods (1st to 4th period) for evaluations of footpad dermatitis. Were evaluated moisture and surface temperature of the litter and the injuries footpad dermatitis. For the qualitative parameters and sensory assessments of broiler of breast meat were selected to 42 days of creating 100 male broiler per cycle that were subjected to the process of slaughtering, collected the muscles Pectoralis major and after 24 hours measured the pH, objective color (L*, a* and b* value), drip loss, cooking loss, shear force and sensory analysis. Chemical conditioner applied in litter was shown to be efficient in adsorb moisture from the litter during the period of high rainfall, and reduced the footpad dermatitis during seasonal periods to 28 days of age of birds and proved to be more efficient to 42 days in periods of transition from the dry to the rainy season and high rainfall, but did not influence the qualitative and sensory parameters of broiler meat. Times with high ambient temperature and relative humidity, as in the first period, may result in changes to the features qualitative of the meat. The birds present lower footpad dermatitis during the transitional period the rain/dry. However the period with highest rain gauge resulted in higher footpad dermatitis in broilers. It is concluded that the compound applied in bed absorbs moisture from the litter and reduces the footpad dermatitis in broilers. The birds present lower footpad dermatitis during the period of transition from the rainy to dry season. The period with highest rain gauge provides greater footpad dermatitis and promotes changes on the qualitative parameters of broiler meat.